Telepraca - nowoczesna, elastyczna forma zatrudnienia i organizacji pracy. Szansa czy zagrożenie? - Szluz, Beata (Oficyna Wydawnicza Politechniki Rzeszowskiej, 2013)
In the era of globalization and an information soci ety we have to deal with changes in our approach to the issue of work. More and more it is becoming a service which is based on the use of modern information technology. One at ypical form of performing work is telework. Telecommuting refers more specifically to work undertaken at a location that reduces commuting time. Major advantages for the employe r are access to an expanded labor supply, a means of hiring part-time staff for cycli cal work, and increased employee productivity. The primary advantages of home telework for the employee are the flexibility it brings to work, increased personal productivity, co st and time savings for able-bodied employees, and a job opportunity for the homebound. Home office workers can be classified into distinct groups. The typical employees current ly home teleworking are: self-disciplined full-time clerical women seeking income at reduced personal expense managerial and professional mothers wanting to nurture young children without dropping completely behind in their careers; and male managers or professionals w ho value the part-time integration of work and family life more than they do competition for further advancement in their organizations. Data support a generalized model of home t eleworkers as individuals who will move in and out of part- or full-time work in home offices for intermittent or longer periods of time, as personal situations change. The origin and formation of the telework definition, its classifications, and the pros and cons in both individual and social dimensions are shown in the article.
Keywords: sociology of social problems; work; telework; employment